Experiences of daily life and oral rehabilitation in oligodontia – a qualitative study. (3rd April 2019) - Saltnes, Solfrid Sørgjerd; Geirdal, Amy Østertun; Saeves, Rønnaug; Jensen, Janicke Liaaen; Nordgarden, Hilde
Abstract: Objective: Quantitative research indicate increased anxiety and poorer mental health related quality of life (QoL) in individuals with oligodontia (congenital absence of six or more teeth). The aim of this qualitative study was to complement and explore the individuals' experiences of life and oral rehabilitation, hopefully improving the care for these patients. Material and methods: Twelve participants (6 females, 6 males, aged 21–48) with oligodontia and experiences of comprehensive dental treatments, consented to participate in a semi-structured interview. The questions in the interview guide were based on previous research and clinical experience and included both open (i.e. how is your life?) and specific questions (i.e. do health care personnel know enough about your condition?). The interview transcripts were coded and analysed using a phenomenological method of analysis. The Regional Ethics Committee approved the study. Results: The following themes grew out of the data; 'feeling of being different', 'the burden of treatment', 'shared decision-making', 'treatment increases self-esteem' and 'use of coping strategies'. Psychological distress and reduced QoL seemed to be related to negative aspects of the themes, which covered unacceptable aesthetics, reduced orofacial function, the long-term process of oral rehabilitation, and negative experiences with healthcare services. The informants used problem focused and emotionally focused strategies to meet these challenges. Finalizing oral rehabilitation and shared decision making were positive aspects of the themes. Conclusion: All themes expressed by the participants were of importance for experienced QoL and psychological distress, and should be acknowledged by health care personnel when planning and performing treatment.